AN OVERVIEW OF THE PERSPECTIVE OF THE DRAGONFLY EFFECT IN THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY IN DIGITAL MEDIA (CASE STUDY OF PT TIP TOP SUPERMARKET’S CSR PROGRAM) - Raden Mas Try Ananto Djoko Wicaksono (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2020)
The aim of the research is to analyze the application of corporate social responsibility on social media in PT Tip Top. The usage of social media in corporate social responsibility activities allows the creation of an interactive dialogue that is horizontal between the company and stakeholders. The research uses qualitative research methods with a case study approach. The author uses research design ‘holistic single case’. This research uses three sources of evidence including direct observation, document analysis, and literature review. This research indicates that the CSR program on online media at PT Tip Top leads to the concept of corporate social marketing.Keywords: corporate social responsibility; implementation corporate social responsibility; social media; digital media